Disclosure of non-financial information in the field of counteracting corruption and bribery in economic practice - Skoczylas-Tworek, Agnieszka (Ujawnianie informacji niefinansowych w zakresie oszustw i nadużyć w praktyce gospodarczej, 2020)
Listed companies are entities of particular interest from the point of view of building a positive image free from the phenomena of fraud. Directive 2014/895/EU of the European Parliament and of the Council of 22 October 2014 imposed an obligation on certain large entities and groups to report non-financial information on corruption and bribery. The aim of this paper is to measure the degree of such data disclosure by market operators in their published statements and reports on non-financial information. The analysis of non-financial data was performed based on the example of the 30 companies listed in the WIG30 Index. The basic research method was quantitative and qualitative analysis which referred to the verification of the degree of detail of published data on corruption and bribery, the standards and guidelines used in this area, and information on whether or not fraud was detected. The conducted research showed that economic operators show considerable restraint in disclosing such data
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 187-198